Lipase-producing ability of bacteria from inasua (fish fermented product) from Central Moluccas, Indonesia - Latusi Anggriani; SRI BUDIARTI; NISA RACHMANIA MUBARIK (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Anggriani L, Budiarti S, Mubarik NR. 2020. Lipase-producing ability of bacteria from inasua (fish fermented product) from Central Moluccas, Indonesia. Biodiversitas 21: 622-628. One of fish preservation techniques through fermentation is Inasua which occurs spontaneously and involves various types of microorganisms. Isolates from Inasua are believed to have the ability to produce lipolytic enzymes. The purpose of this study was to identify potential bacterial isolates isolated from Inasua and to determine their lipase producing ability. The confirmation test of lipase-producing ability was conducted by inoculating the microbes into media containing Nutrient agar (NA), olive oil, and rhodamin-B. Lipolytic bacteria were detected using a screening method with UV light. From the results, there were 5 isolates of bacteria that showed lipolytic activity as IG 3.1, IG 6, IG 10, IG 12, IG 66. Lipase assay was determined using spectrophotometric method with p-nitrophenyl palmitate (pNPP) as a substrate and titration method with olive oil as a substrate. The enzyme showed maximum activity at pNPP as a substrate. IG 6 and IG 12 gave the highest activity from lipase assay. Growth and production curves were created before partial purification was carried out. The results of the curves showed that the optimum activity of IG 6 and IG 12 were in the stationary phase with value 38.16 U.mg-1 protein and 7.01 U.mg-1 protein, respectively. After ammonium sulfate precipitation, the activity of the lipase IG 6 and IG 12 were found to be 39.65 U.mL-1 and 37.05 U.mL-1, respectively. During optimization, the enzyme showed maximum activity at pH 8/70°C temperature. Molecular identification by using the 16S rRNA gene and phylogenetic analysis showed that isolates IG 6 and IG12 are closely related to Bacillus paramycoides and Bacillus kochii, respectively.